The unsuccessful shopping centre : ruling out the phenomena and causes / Muhammad Zulhilmi Mohd Yusof and Aida Affina Abd Ghani - Mohd Yusof, Muhammad Zulhilmi; Abd Ghani, Aida Affina (2018)
Shopping Centre is the largest industry and the most dynamic and rapidly developing industries. The retail shopping outlet in Malaysia is growing and there are tremendous opportunities to get involved in the sector. But nowadays shopping mall in Malaysia must face competitors from other shopping Centres to run the business and earn income. They do not have control in developing the shopping Centre. This may lead to unsuccessful and failure at the shopping Centre. This research aims to investigate the unsuccessful mall in Malaysia and one shopping Centre was selected. The objectives of the study are to analyze landscape of the shopping Centre, to identify factor and causes of unsuccessful mall, and to find the rank of unsuccessful mall. This research has used quantitative method by interviewing three main respondents such as management and maintenance, 3 users, and 3 tenants to gather the perception of shopping Centre. Then we used observation method to observe the layout and design of the shopping Centre. After that we analysed all the interview and highlight the themes that emerged from the interview.